IDENTIFIKASI PENYAKIT VASCULAR STREAK DIEBACK (VSD) DAN TINGKAT SERANGAN SERTA PENGARUHNYA PADA PERTUMBUHAN KAKAO DI TIGA DESA KEC. PALOLO KAB. SIGI - Syarif, Mohammad (JSTT, 2016)
The aim of this study is to identify VSD  attacks  to cocoa crop in three villages in Palolo. b.analize  the way of VSD   infecting  cocoa crop in three villages, in  Palolo, Sigi. c.how to cut  the attack and control the damage caused by VSD to cocoa in three villages in Palolo. This study using identification method. The  research method  that is conducted through observation of the leaves, twigs and branches of the cocoa plant which suspect  attacked  by VSD in the field and observation in laboratory to ensure that the attack VSD on cocoa in the three villages in Palolo actually happened , as well as focusing on actual problems of the development of  VSD. The research was conducted in three villages names  Ampera, berdikari  and  Rejeki village in Palolo. Determination of the location of the research done on purpose (purposive method), with the consideration that all three of the village is the center of  development of  cocoa  production in  Palolo.  This research was conducted for three months from January to April 2015  and then continued  by observing VSD in the laboratory of pest and disease Agriculture faculty, Tadulako University. VSD has been  informed  attacking   almost all the province which producing cocoa   in Indonesia. In 2000, there were VSD attacks reaches 6000 ha with yield losses  Rp 405 643 680 000 / year.  The number of the attack until May 2001 reached 70 000 ha with a loss of billions  rupiah (Ditjenbun, 2007). The observation  result  like contained  in Tabel 1 show that in average the intensity  attacks of VSD  from the research site showed that  cocoa  in Berdikari  has the highest VSD attack it is 16.9%, on the contrary VSD attack  in Ampera  and Rejeki are low attack each of  them  12 , 5% and 12.1%. This shows that in all three villages have been found the attack of VSD as seen in the field, where the characteristic of  attack ,the leaves infected  of VSD changes the color  to yellow with green patches on the surface of the leaves, and the leaves will eventually fall. In the former  leaves holder  which is affected by VSD will appear visible three point brown indicates that the plant has been attacked by VSD, meanwhile on the twig attacked, if observed in detail and touched with fingers, it would seem that the surface of twig is uneven  because it has been Swelling occurs on the surface, so that within a certain time the branch would dry up and will seem toothless, this happens because the VSD disease has progressed on the xylem and hinder the process of transformation of food to other plant tissues. These events will cause significant changes in plants, from healthy plants become dry due to the intake of food that goes into the xylem become obstructed. With the special mark left by VSD on branches and twigs of cocoa plants in three villages can be assumed that in  Palolo, there has been a VSD attacks caused by fungi Oncobasidium theobromae (Basidiomycetes).